The Determinants of Career Selection as a Public Accountant: The Role of a Financial Reward Moderator : Determinan Pemilihan Karir Sebagai Akuntan Publik : Peran Moderator Financial Reward - Rahayu, Ruci Arizanda; Abidin, Fityan Izza Noor (Journal of Accounting Science, 2023)
This study aims to identify the Factors Influencing the Career Selection of Accounting Students as Public Accountants by using financial rewards as a moderating variable for UMSIDA and UBHARA Accounting students. The population or subjects in this study consisted of Accounting Study Program students from the Muhammadiyah Sidoarjo University and Bhayangkara University Surabaya class of 2018. In this study, a quantitative method was used by distributing questionnaires online. By using Slovin’s formula, 80 respondents filled out the research questionnaire. The results of the study show that professional training, social values, work environment, and labor market considerations influence the choice of a career as a Public Accountant. As a moderating variable, financial reward strengthens the influence of professional training, social values, work environment, and labor market considerations on choosing a career as a Public Accountant. This research has implications for final-year Accounting students in determining careers as Public Accountants.